Modelos de redes de mapas acoplados para interações herbívoro-predador - Parigi, Aline da Rosa (2013)
In this work we propose a discrete predator-prey model with the purpose of analyzing the spatio-temporal dynamics of herbivorous and their predators. For that, we explicitly consider the dispersion of both species through Coupled Map Lattice models, that is, systems of difference equations coupled by dispersal. We suppose that the prey population presents density-dependent growth and predators, Holling type II functional response. In order to analyze the effects of prey-taxis showed by predators, which means, that predators direct their movement to regions of high prey densities, we computationally implemented our model for different movement schemes: difusion for both species, immobile prey and taxis for predators and, difusion for prey and taxis for predators. We conclude that the dispersal behavior of predators and preys plays a crucial role on their spatio-temporal dynamics and hence cannot be omitted when modeling predator-prey interactions.